Comparative effectiveness and safety of immunotherapeutic strategies in ovarian cancer: a systematic review and network meta-analysis - Wang, Xinyao; Zhang, Yuli; Xie, Wei; Liu, Haiying; Cui, Lianghui; Feng, Min (Frontiers in Oncology, 2025)
BackgroundOvarian cancer remains the most lethal gynecologic malignancy, with poor survival despite standard therapies. Immunotherapy represents a promising option, yet the comparative efficacy and safety among different immunotherapies are unclear. This network meta-analysis aimed to evaluate and rank multiple immunotherapeutic strategies for ovarian cancer.MethodsA systematic search of PubMed, Embase, Medline, PsycINFO, Cochrane Central Register of Controlled Trials, and Web of Science was performed through May 31, 2025. Randomized controlled trials (RCTs) comparing immunotherapies were included. Outcomes were overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), treatment-related adverse events (TRAEs), and grade ≥3 adverse events. Bayesian network meta-analysis was conducted using random-effects models, calculating standardized mean differences (SMDs) or mean differences (MDs) with 95% confidence intervals (CIs) for continuous variables, and odds ratios (ORs) with 95% CIs for categorical variables.ResultsTwenty-six RCTs involving 5,982 patients were included. Cancer vaccines (CV) (HR = 0.56, 95% CI 0.43–0.73) and dual immune checkpoint blockade (DICB) (HR = 0.65, 95% CI 0.46–0.92) significantly improved OS compared with controls. CV also prolonged PFS (SMD = 0.95, 95% CI 0.16–1.75). CTLA-4 inhibitors markedly increased ORR (OR = 99.32, 95% CI 1.18–8360.43), though no significant DCR differences were observed. PD-1 inhibitors demonstrated the best safety profile, reducing grade ≥ 3 AEs (OR = 0.16, 95% CI 0.08–0.33) and overall TRAEs versus other immunotherapies.ConclusionCV and DICB yielded the most consistent survival benefits, while PD-1 inhibitors showed superior safety. These findings support tailored, biomarker-informed immunotherapy approaches and combination strategies to optimize efficacy and tolerability in ovarian cancer. Further head-to-head trials are warranted to confirm these results.Systematic Review RegistrationPROSPERO (CRD420251083861).